The effects of mythomycin C, hylan Gf20 and honey combinations on adhesion formation in laparotomized rats (Annals of Medical Research, 2021)
None
Keywords: Adhesion; Mitomycin-C; Hylan Gf-20; Honey; Laparotomy; Rats.